FINAL STAGES OF THE METAMORPHIC EVOLUTION OF THE TANAéLV BELT, KOLA PENINSULA, BALTIC SHIELD: EVIDENCE FROM U-PB DATING ON ZIRCON, TITANITE, AND RUTILE - Kaulina T.V.; Kislitsyn R.V.; Apanasevich E.A. (My University, 2004)
Field and isotopic evidence suggests the following sequence of metamorphic events for the Tanaélv belt, as determined at the Yavrozero area. The peak of high-temperature amphibolite (and, presumably, granulite) metamorphism related to the main deformation stage is constrained between 1945 ± 8 Ma (magmatic crystallization age of anorthosites) and 1928 ± 10 Ma (age of a garnet-pyroxene dike cutting across foliated anorthosites). Metamorphism of a garnet pyroxenite dike to high-temperature amphibolite facies suggests that high-temperature transformations continued after 1928 Ma. The exhumation-related decompression and cooling stage, which was marked by abundant zircon crystallization in the rocks of the Tanaélv belt and LGB, began at 1920-1916 Ma. The exhumation was followed by lower grade amphibolite metamorphism between 1909 and 1898 Ma, which was recorded in the formation of high-U zircons. Rock cooling to 450° C, as defined by the rutile age, occurred at 1880-1870 Ma. Age data on titanite and rutile having different closure temperatures of the U-Pb system made it possible to calculate the cooling gradient of the rocks from 700 to 450°C at ∼6°C/Ma.